2018
DOI: 10.1088/1742-6596/1025/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Automatic vehicle counting using background subtraction method on gray scale images and morphology operation

Abstract: Abstract. Traffic monitoring on road needs to be done, the counting of the number of vehicles passing the road is necessary. It is more emphasized for highway transportation management in order to prevent efforts. Therefore, it is necessary to develop a system that is able to counting the number of vehicles automatically. Video processing method is able to counting the number of vehicles automatically. This research has development a system of vehicle counting on toll road. This system includes processes of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Another study presented by Li et al provides a YOLO-vocRV model for vehicular detection application, which enables detecting multiple targets of different traffic densities [9]. rough the study evaluation, the authors recognize that the proposed model gives suitable detection rate; however, it gives high false detection rate especially in low training dataset [10]. Sheng et al provide the concept of using R-CNN model to increase the dataset of traffic detection datasets [11].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study presented by Li et al provides a YOLO-vocRV model for vehicular detection application, which enables detecting multiple targets of different traffic densities [9]. rough the study evaluation, the authors recognize that the proposed model gives suitable detection rate; however, it gives high false detection rate especially in low training dataset [10]. Sheng et al provide the concept of using R-CNN model to increase the dataset of traffic detection datasets [11].…”
Section: Related Workmentioning
confidence: 99%
“…It is used to classify objects into its attributes or features into K number of clusters. Here, K represents a positive integer value [10,14]. K-means begins with the selection of a single centroid at random [19].…”
Section: Implementation Of Convolutional Neural Network (Cnn)mentioning
confidence: 99%
“…Moreover, some researcher even combined it with Machine Learning to help improve recognition accuracy [7,8]. We could not ignore the fact that morphology operation is one of the most popular techniques to be used in object recognition [9,10]. The reason for such popularity is that morphology operation while being not very complicated and costly; it could expose the whole structure of an object to ease the recognition of the desired object or to detect an undesired object to be removed from the image.…”
Section: Related Workmentioning
confidence: 99%
“…The author in [14] reported the dimming is accomplished by adjusting the average current in the LEDs through pulse width modulation of a switch in series with the load. Meanwhile, [15] suggested that a camera with image processing software is used to recognize the target. The color, size, and variant of blinking of the LED markers detected by the camera is the main limiting factor of this method.…”
Section: Introductionmentioning
confidence: 99%